Diabetes mellitus in long-term survivors with colorectal, breast, or prostate cancer: prevalence and prognosis : a population-based study - Yang, Keyi; Doege, Daniela; Thong, Melissa S. Y.; Koch, Lena; Weißer, Linda; Bertram, Heike; Eberle, Andrea; Holleczek, Bernd; Nennecke, Alice L.; Waldmann, Annika; Zeißig, Sylke; Pritzkuleit, Ron; et al. (Cancer, 2023)
Background Patients with cancer are at increased risk of diabetes mellitus (DM). Previous studies on the prevalence and prognostic impact of DM in cancer survivors were limited by small sample sizes or short follow-up times. We aimed to compare the patient-reported prevalence of DM in long-term cancer survivors (LTCS), who survived 5 years or more after cancer diagnosis, with that in cancer-free controls, and to estimate the mortality risk among LTCS according to DM status. Methods Our population-based cohort comprised 6952 LTCS diagnosed with breast, colorectal, or prostate cancer between 1994 and 2004, recruited in 2008-2011 (baseline), and followed until 2019. A total of 1828 cancer-free individuals served as controls. Multivariable logistic regression was used to compare the prevalence of DM in LTCS and controls, and according to covariates at baseline. Mortality among LTCS according to DM was assessed by Cox proportional hazards regression. Results A total of 962 (13.8%) LTCS at baseline reported DM. Prevalence of DM in LTCS was not higher than in cancer-free controls, both at baseline (odds ratio, 0.80; 95% CI, 0.66-0.97) and at follow-up (odds ratio, 0.83; 95% CI, 0.67-1.04). Prevalence of DM in LTCS was associated with cancer site, older age, lower education, higher socioeconomic deprivation, higher body mass index, physical inactivity, other comorbidities, and poorer prognosis (adjusted hazard ratio [all-cause mortality] = 1.29; 95% CI, 1.15-1.44). Conclusion DM in LTCS is prevalent, but not higher than in cancer-free population controls. Cancer survivors with concurrent DM are at a potentially higher risk of death. Plain Language Summary Cancer and diabetes mellitus (DM) are two serious threats to global health. In our study, prevalence of DM in long-term cancer survivors who survived 5 years or more after cancer diagnosis was not higher than in cancer-free controls. This should not be interpreted as an indication of a lower risk of DM in cancer survivors. Rather, it highlights the potentially poor prognosis in diabetic cancer survivors. Therefore, keeping a continuous satisfactory DM and hyperglycemia management is essential during long-term cancer survivorship.
Gesehen am 18.06.2024